Low Prevalence of SARS-CoV-2 in Farmed and Free-Ranging White-Tailed Deer in Florida - Savannah G. Grace; Kristen N. Wilson; Rayann Dorleans; Zoe S. White; Ruiyu Pu; Natasha N. Gaudreault; Konner Cool; Juan M. Campos Krauer; Laura E. Franklin; Bambi C. Clemons; Kuttichantran Subramaniam; Juergen A. Richt; et al. (Viruses, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been detected in multiple animal species, including white-tailed deer (WTD), raising concerns about zoonotic transmission, particularly in environments with frequent human interactions. To understand how human exposure influences SARS-CoV-2 infection in WTD, we compared infection and exposure prevalence between farmed and free-ranging deer populations in Florida. We also examined the timing and viral variants in WTD relative to those in Florida’s human population. Between 2020 and 2022, we collected respiratory swabs (N = 366), lung tissue (N = 245), retropharyngeal lymph nodes (N = 491), and serum specimens (N = 381) from 410 farmed and 524 free-ranging WTD. Specimens were analyzed using RT-qPCR for infection and serological assays for exposure. SARS-CoV-2 infection was detected in less than 1% of both northern Florida farmed (0.85%) and free-ranging (0.76%) WTD. No farmed deer possessed virus-neutralizing antibodies, while one free-ranging WTD tested positive for SARS-CoV-2 antibodies (3.45%). Viral sequences in infected WTD matched peaks in human cases and circulating variants, indicating human-to-deer spillover but at a lower frequency than reported elsewhere. Our findings suggest a reduced risk of SARS-CoV-2 spillover to WTD in northern Florida compared to other regions, highlighting the need for further research on transmission dynamics across North America.